Injuries Reported and Recorded for Adults with Intellectual Disabilities Who Live with Paid Support in Scotland: a Comparison with Scottish Adults in the General Population. Issue 2 (10th February 2016) - Petropoulou, Evangelia; Finlayson, Janet; Hay, Margaret; Spencer, Wendy; Park, Richard; Tannock, Hugh; Galbraith, Erin; Godwin, Jon; Skelton, Dawn A.
Abstract : Background: Providers of supported living services to adults with intellectual disabilities (IDs) in the United Kingdom have procedures in place to monitor injuries; this provides opportunity to learn about the injuries being reported and recorded. The aim was to determine the incidence, causes and types of injuries experienced by 593 adults with intellectual disabilities who live with paid support in a 12‐month period. Method: Injury data, collected via a standard electronic injury monitoring system, were compared with data collected for a matched sample of the general population in the same year. Results: The adults with intellectual disabilities experienced a higher rate of injury. Falls were the commonest cause of injury for both samples, but significantly more so for the adults with intellectual disabilities. Conclusions: The higher rate of injuries, particularly minor injuries, being reported suggests a culture of injury reporting and recording within these supported living services. Electronic injury monitoring is recommended for organizations providing supported living services for adults with intellectual disabilities.